CALCULATION OF RELATIVE PERMEABILITY BASED ON POROUS NETWORK MODEL - Al-Ghifari, Hakim
Relative permeability plays an important role in reservoir characterization, reservoir engineering, soil science, petroleum engineering, and other industries. Therefore, more effective and efficient methods have been developed to determine relative permeability. The main objective of the conducted research is to determine relative permeability data and compare it using the capillary pressure models of Purcell, Corey, and Brooks-Corey to identify the most suitable model for use. The research is carried out by conducting drainage porosimetry simulations using the OpenPNM framework with the Python programming language. From the simulations, data such as capillary pressure and non-wetting phase saturation are obtained. Subsequently, this data is processed to obtain other parameters such as wetting phase saturation, normalized saturation, and pore size distribution index, enabling the calculation of relative permeability using the capillary pressure models of Purcell, Corey, and Brooks-Corey. The results of these calculations are then plotted with normalized saturation and subjected to analysis to determine the most appropriate and accurate capillary pressure model for determining relative permeability.